An Urban Rail Traction Power Supply Rectifier and Its Circulating Current Suppression Scheme - WANG Lunyue; WANG Xiong; CHEN Jielian; WU Xuefeng; WENG Xingfang (Kongzhi Yu Xinxi Jishu)
In urban rail traction power supply system, DC catenary grounding is a common fault. As IGBT devices of PWM rectifier have no ability to withstand short-circuit current, controllable traction power supply rectifier equipment usually adopts PWM rectifier and diode rectifier in parallel mode to improve short-circuit withstand ability, but PWM rectifier and diode rectifier in direct parallel connection will introduce circulating current, resulting in damage to the diode rectifier. In order to solve the circulating current problem, firstly, the advantages and disadvantages of the common scheme of circulating current between PWM rectifier and diode rectifier are analyzed. Then, a new topology is proposed, which requires no additional hardware investment, and the circulating current is suppressed within the safe range by means of a specific angle carrier phase shift modulation algorithm between multiple PWM rectifiers. Finally, a simulation model of the traction power supply system is established based on the proposed rectifier equipment, and the system simulation and experimental verification are carried out. Experimental results show that the diode rectifier branch current is only 6.7 A when the equipment is running. The simulation results are consistent with the experimental results, and the rectifier equipment and its control strategy proposed in this paper can effectively suppress the circulating current, which verifies the effectiveness and feasibility of the scheme.